2001
DOI: 10.1073/pnas.051612298
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the restriction-modification systems in Helicobacter pylori

Abstract: Helicobacter pylori is a Gram-negative bacterial pathogen with a small genome of 1.64 -1.67 Mb. More than 20 putative DNA restrictionmodification (R-M) systems, comprising more than 4% of the total genome, have been identified in the two completely sequenced H. pylori strains, 26695 and J99, based on sequence similarities. In this study, we have investigated the biochemical activities of 14 Type II R-M systems in H. pylori 26695. Less than 30% of the Type II R-M systems in 26695 are fully functional, similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 30 publications
8
164
1
Order By: Relevance
“…This indicates that each MTase of a particular R-M system is not a product of gene duplication but was acquired/evolved independently. Recent studies on the diversity of R-M systems in Helicobacter pylori provide facts endorsing such a notion (Nobusato et al, 2000a, b;Lin et al, 2001). In vivo experiments with the BcnI R-M system show that M.BcnIB alone is sufficient to support the growth of E. coli cells carrying the BcnI ENase gene; this could not be demonstrated for M.BcnIA (Vilkaitis et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…This indicates that each MTase of a particular R-M system is not a product of gene duplication but was acquired/evolved independently. Recent studies on the diversity of R-M systems in Helicobacter pylori provide facts endorsing such a notion (Nobusato et al, 2000a, b;Lin et al, 2001). In vivo experiments with the BcnI R-M system show that M.BcnIB alone is sufficient to support the growth of E. coli cells carrying the BcnI ENase gene; this could not be demonstrated for M.BcnIA (Vilkaitis et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Further analyses revealed that only some of these systems retain enzyme activity (195,198). In some of the inactive systems, REases are truncated while retaining the functional MTase gene.…”
Section: R-m Systems Of Helicobacter Pylorimentioning
confidence: 99%
“…The well-known type II restriction-modification systems constitute the primary defensive mechanism against foreign DNA and can, remarkably, account for greater than 4% of the genome for some bacteria (Helicobacter pylori) (179). The type II restriction enzymes cleave foreign DNA into linear fragments that are substrates for more extensive nucleolytic degradation by the RecBCD enzyme (85,121,171,255).…”
Section: Foreign Dna Degradationmentioning
confidence: 99%